Remagnetization of serpentinite during deformation: evidence from a fossil oceanic transform fault zone of the Troodos ophiolite - QI,L; Allerton,S; Muxworthy,A; Zhang,Y; Gergov,H (Journal of Geophysical Research: Solid Earth, 2025)
Serpentinization and associated chemical remagnetization of ultramafic rocks are common in tectonically active oceanic zones such as transform zones; however, it remains unclear how chemical remagnetization occurs during the deformation of serpentinite. This study aims to discuss this magnetization process with evidence from a serpentinite shear zone within the fossil transform fault of the Troodos ophiolite. We examine how serpentinite microstructures, serpentine polytypes, iron behaviors, rock magnetic properties and paleomagnetic directions evolve with increasing shearing deformation—a process that provides pathways for serpentinization fluid circulation. As serpentinite deformation increases from massive-fractured serpentinite adjacent to the shear zone to scaly and phyllonitic serpentinites within the shear zone, rock microstructure changes from unoriented mesh textures to oriented ribbon and fibrous structures. Meanwhile, the dominant serpentine mineral shifts from lizardite to chrysotile, indicating dynamic recrystallization during increasing deformation, likely resulting from elevated water/rock ratios driven by hydrothermal circulation. Rock magnetic results suggest that highly deformed scaly and phyllonitic serpentinites contain coarser magnetite grains and higher magnetite concentration compared to the less deformed massive-fractured serpentinites. These coarser magnetite grains are also attributed to higher water/rock ratios within the shear zone. More magnetite forms due to the iron released from the replacement of iron-rich lizardite by iron-poor chrysotile. The formation of magnetite records remagnetization, which helps reconstruct the deformation history of tectonically active zones. For example, paleomagnetic directions of the differentially deformed serpentinites in Troodos ophiolite indicate clockwise block rotations of up to 90°, providing evidence for dextral slip along a fossil transform fault.